Dinamika Pembebanan Jaminan Fidusia Terkait Dengan Prinsip Spesialitas - Ferdiansyah Putra Manggala (Jurnal Ilmu Kenotariatan, 2023)
The principle of specializing fiduciary guarantees in consumer financing agreements is one of the principles that must be fulfilled, in order to provide legal certainty to both fiduciary recipients and fiduciary recipients, particularly regarding the right to ownership of collateral. If the consumer financing agreement is not fulfilled by the principle of specialization, then there is no legal certainty in the agreement. Every object that is burdened with a fiduciary guarantee must be registered at the fiduciary registration office for the birth of the fiduciary guarantee. A new fiduciary guarantee is said to be born if it has been registered so that a fiduciary certificate is issued which has executive power if in the future the debtor defaults. So that the creditor in the settlement of default is not based on a power of attorney but based on a fiduciary certificate which has the same strength as a court decision that has permanent legal force. The methodology used in this study is the normative juridical methodology and the approach used is a conceptual approach and a statutory approach. The thinking framework used is descriptive method in this study. Conclusion: Based on the consumer financing agreement issued by the consumer financing institution, it can be concluded that the consumer financing agreement does not provide a fiduciary guarantee. A fiduciary guarantee is born if the object encumbered with the fiduciary guarantee has been registered at the regional office of the Ministry of Law and Human Rights in the province. Consumer financing agreements issued by consumer financing institutions do not fulfill the principle of legal specialization of material guarantees. Based on the definition of the principle of specialization, security rights, fiduciary rights and mortgages can only be imposed on goods that have been registered in the name of a certain person. KEYWORDS:: SKMHT, Time Limit, Creditors.